Diversity of onion nematode fauna in agrocenoses of different altitudinal zones in Fergana Valley, Uzbekistan - SARDORBEK KAMBAROV; KHOLISA ESHOVA; SARDORBEK NARZULLAYEV; FARKHOD TO‘XTASINOV; ODILJON ZOKIROV; ZAFARBEK TURDIEV; BEKZOD OTAKULOV; SHAHLO TURSUNOVA; SHAHBOZ KHUJAMOV (Society for Indonesian Biodiversity, 2025)
Abstract. Kambarov S, Eshova K, Narzullayev S, To’xtasinov F, Zokirov O, Turdiev Z, Otakulov B, Tursunova S, Khujamov S. 2025. Diversity of onion nematode fauna in agrocenoses of different altitudinal zones in Fergana Valley, Uzbekistan. Biodiversitas 26: 4479-4489. During research conducted from 2020 to 2024, the biodiversity of nematode fauna associated with onion plants (Allium cepa) cultivated in agrocenoses across different altitudinal zones of the eastern part of the Fergana Valley was thoroughly investigated. As part of the study objectives, a total of 276 samples were collected from the onion root system and its surrounding rhizosphere soils during the spring, summer, and autumn seasons using the route survey method, of which nematodes were detected in 245 samples. The samples were processed following Berman's funnel technique. Based on the obtained results, 39 nematode species belonging to 7 orders and classified within the classes Adenophorea and Secernentea were identified in the onion root system and rhizosphere soils, representing 22 genera. An uneven distribution of the identified species across the altitudinal zones was observed. Within the faunal composition, species of the order Rhabditida were the most diverse in terms of species richness. The study demonstrated that nematode species composition and ecological structure vary significantly depending on the altitudinal zones. In the lower hill zone, 34 species were recorded, whereas 30 species were documented in the upper hill zone and 12 species in the lower mountain zone. This indicated a link between these patterns and the region's ecological characteristics. According to Bongers' classification, nematodes identified in onion fields were assigned as follows: 7 species to the Cp-1 group, 26 species to Cp-2, 2 species to Cp-3, 3 species to Cp-4, and 1 species to Cp-5. Aporcelaimellus obtusicaudatus (C-p 5), which occurred across all three zones, is considered a highly specialized and adaptable species. The results of the study provide a scientific basis for a deeper understanding of the region's biodiversity and for managing the dynamics of nematode fauna in agrocenoses.